Application of Exogenous Iron Alters the Microbial Community Structure and Reduces the Accumulation of Cadmium and Arsenic in Rice (Oryza sativa L.) - Tingting Li; Jiayuan Li; Xin Zhan; Xueli Wang; Bing He; Feishu Cao; Changjun Liao; Yuefeng Yu; Zengyu Zhang; Junhui Zhang; Bei Li; Jiancheng Chen; et al. (Nanomaterials, 2022)
Cadmium (Cd) and arsenic (As) contamination of soil has been a public concern due to their potential accumulation risk through the food chain. This study was conducted to investigate the performance of ferrous sulfate (FeSO4) and ferric oxide (Fe2O3) nanoparticle (Nano-Fe) to stabilize the concentrations of Cd and As in paddy soil. Both Fe treatments led to low extractable Cd and the contents of specifically sorbed As contents, increased (p < 0.05) the Shannon index and decreased (p < 0.05) the Simpson diversity indices compared with the control. Nano-Fe increased the relative abundances of Firmicutes and Proteobacteria and decreased the abundances of Acidobacteria and Chloroflexi. Moreover, the addition of both forms of Fe promoted the formation of Fe plaque and decreased the translocation factor index (TFs) root/soil, TFs shoot/root, and TFs grain/shoot of Cd and As. These results suggest that exogenous Fe may modify the microbial community and decrease the soil available Cd and As contents, inhibit the absorption of Cd and As by the roots and decrease the transport of Cd and As in rice grains and the risk intake in humans. These findings demonstrate that soil amendment with exogenous Fe, particularly Nano-Fe, is a potential approach to simultaneously remediate the accumulation of Cd and As from the soil to rice grain systems.